Pengaruh Kinerja Keuangan Terhadap Pembiayaan Murabahah Dengan Dana Pihak Ketiga Sebagai Pemoderasi - Herawati Khotmi (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
This study aims to investigate the effect of Capital Adequacy Ratio, Financing to Deposit Ratio, Non-Performing Financing on murabahah financing, to verify the effect of Capital Adequacy Ratio on murabahah financing with Third Party Funds as a moderating variable, to assess the effect of Financing to Deposit Ratio on murabahah financing. with Third Party Funds as moderating variable and to verify Non-Performing Financing on murabaha financing with Third Party Funds as moderating variable. This study used secondary data that obtained from ojk.co.id. Number of population in this study was 14 (fourteen) Islamic commercial banks registered in 2020 in Indonesia, which obtained with purposive sampling. The sampling criteria were Islamic banks with book category 3 and core capital between 5 trillion to 30 trillion rupiah. The number of samples was 4 banks with 3 (three) book categories, namely Bank Syariah Mandiri, Bank Negara Indonesia Syariah, Bank Rakyat Indonesia Syariah, National Syariah Pension Savings Bank. Data was analyzed by using eviews version 9. The analysis results indicate that Non-Performing Financing, Capital Adequacy Ratio, Financing to Deposit Ratio have an effect on murabahah financing, the Third-Party Funds moderated the effect of capital adequacy ratio on murabahah financing, Third Party Funds moderated the effect of Financing to Deposit Ratio on murabahah financing, Third Party Funds did not moderate the effect of Non Performing Financing on murabahah financing.